Penerapan Model Pembelajaran Inkuiri Terbimbing Untuk Meningkatkan Aktivitas Dan Hasil Belajar IPA Siswa Kelas V SD INPRES 2 Kayumalue Ngapa - Erlina Erlina; Amram Rede; Sahrul Saehana (Universitas Tadulako, 2016)
The purpose of this study was to be improve activity and science achievement at fifth grade SD Inpres 2 Kayumalue Ngapa by application of guided inquiry learning model. This study is classroom action research that refers to the Kemmis and Taggart model which consists of four stages namely: planning, action, observation, and reflection. The Learning was done for 3 cycles, each cycle conducted in three meetings. The data was analyse by used qualitative analysis techniques for learning process and quantitative analysis for learning outcomes. Based on classical completeness and absorption, it could be said the achievement of each end of the cycle of 20 students always increasing. Based on the percentage of achieved of students and teacher activity from the first cycle until third cycle the achievement were increased. Achievement of completeness criteria and absorption by way classical, influenced by the optimal activity of students and teachers during the learning takes place.